Veddah women : impact of t[r]anslocation from a forest environment to agricultural settlements - Jayasena, Asoka; CENWOR (Organization : Sri Lanka) (Colombo : Centre for Women's Research, 1994)
Study restricted to Henanigala village where the families now reside and Dambana, the area from where the translocated families hailed.
Keywords: Ethnology -- Sri Lanka; Women, Viddha -- Social conditions -- Sri Lanka -- Hananigala; Women, Viddha -- Social conditions -- Sri Lanka -- Dambana; Vedda (Sri Lankan people) -- Social conditions